Toward an Anthroporelational Humanism: A Configuration of Zoocriticism in Vietnamese Postcolonial Literature - Hung Kieu; Phuong Uyen Phan La; Bui Kim Quynh Giang; Tuan Anh Pham (Journal of Language and Literature, 2026)
Recently, posthumanism has emerged as a vital lens for elevating nonhuman voices in contemporary literature. However, in the Vietnamese postcolonial context, where the legacies of war and colonialism remain profound, fully displacing the human subject is challenging. This qualitative textual analysis examines a purposive sample of short stories by writers Bùi Ngọc Tấn and Nguyễn Quang Thân to explore how animal representations function as a site of negotiation between humanism and posthumanism. Utilizing close reading and thematic analysis, the study investigates specific human-animal entanglements, such as the anthropomorphized grief of the dog in “The Puppy” and the institutionalized exploitation of the goat in “The Man Who Made Earthquakes”. By analyzing these textual moments through postcolonial ecocriticism and zoocriticism, the research illustrates how these narratives disrupt the strict human-animal divides established by colonial discourse. The findings suggest that these texts operate within a mode of anthroporelational humanism, a perspective that maintains human-centered ethical concerns while granting animals distinct narrative subjectivity. Rather than reducing animals to mere background symbols, these stories reveal a shared ground of vulnerability, where humans and animals process colonial trauma together. The article concludes that this relational framework enriches postcolonial discourse, demonstrating how interspecies empathy serves as a crucial mechanism for cultural recovery and the rearticulation of identity.